Enhancing Service Quality And Operational Efficiency In Restaurants Through Agile-Based Vendor Management Systems - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research addresses the development of Agile-based vendor management systems within the context of the restaurant industry. The main problem discussed is the challenges in vendor management that affect service quality and operational efficiency in restaurants. The research methodology includes system requirement analysis, application design and implementation, and system testing and evaluation. The research findings indicate that a deep understanding of the needs and challenges in vendor management can result in a responsive and effective system. Integrating key features such as vendor registration, vendor performance tracking, inventory management, and reporting functions has improved restaurant service quality and operational efficiency. The contribution of this research lies in a better understanding of the development of Agile-based vendor management systems and their application in enhancing overall restaurant performance.